Additive‐Free, Robust H2 Production from H2O and DMF by Dehydrogenation Catalyzed by Cu/Cu2O Formed In Situ. Issue 28 (12th June 2017) - Zhang, Sai; Ma, Yuanyuan; Zhang, Huan; Zhou, Xuemei; Chen, Xiao; Qu, Yongquan
Abstract: Hydrogen production from organic/inorganic hydrides is a promising strategy for the development of novel clean energy resources to replace fossil fuels and satisfy ever‐increasing energy demands. Most current processes involve small flammable chemicals and are catalyzed by noble metals in basic media with the release of the greenhouse gas CO2 . Herein, we describe an alternative pathway for highly efficient and robust H2 production through a dehydrogenation reaction between water and N, N ‐dimethylformamide catalyzed by Cu/Cu2 O catalysts formed in situ. The catalysts exhibit high and robust activity for H2 production. Importantly, the formation of H2 as the sole gas and the valuable by‐product N, N ‐dimethylaminoformic acid make this process clean and valuable with 100 % atom economy. Abstract : Day after day after day… A dehydrogenation reaction between N, N ‐dimethylformamide (DMF) and water was promoted by a Cu/Cu2 O catalyst formed in situ to generate hydrogen gas (see picture). The catalysts exhibited excellent activity and continuously produced hydrogen for at least 17 days with a turnover number of 87 725. This process is potentially waste‐free, as the by‐product dimethylaminoformic acid is a valuable chemical.